DESCRIPTION OF CUSTOMS AND TRADITIONS IN SHIA COMMUNITIES - Nig‘matullayev Ibrohim Ma’ruf o‘g‘li (Scholar Express Journal, 2024)
This article describes information as to the customs and traditions of shia communities and their unique characteristics. Together with this, in this article gives information about Navruz holiday and the history of its origin, “Haft sin” table which is considered a tradition of Navruz holiday and its characteristics.
Keywords: Iranian; shia communitie; imam; holiday